PENERAPAN GOOD GOVERNANCE DI DESA KOTO TALUK KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI PADA TAHUN 2016 - Suradi, Igo; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
A research has been conducted to determine the leadership role of village heads in realizing good governance in the village of Koto Taluk. This research is a qualitative research with techniques used in data collection through interviews and documentation. The results showed that 1) the village head of Koto Taluk in running his government was always transparent, both before making a decision, the decision making process and the implementation of the decision, 2) the communication built by the village head with the village community was very intense and intimate, 3) the participation of the village community very high and active in village government, it can be seen from the mutual cooperation that is often done in the village, 4) In realizing good governance, the village head has an active role in increasing the participation of village communities, 5) In formulating a policy the village head always prioritizing deliberations with village communities to implement agreements in order to be implemented, 6) The village head has the authority and delegates to village community leaders to be able to run evenly so as to create good alignment and governance.  Keywords : Role, Leadership, Good Governance